A STRUCTURAL EQUATION MODELLING APPROACH TO DEVELOPMENT OF SOCIAL MEDIA BRAND ATTITUDE MODEL (SMBAM) - A STUDY - Neeraja, V. R.; Mohan, M. Nirmala; Kumar, P. M. Ramesh (International Journal of Psychosocial Rehabilitation, 2020)
This empirical study was aimed to explore the determinants of social media brand attitude of social media networking sites users in Chennai city of Tamil Nadu. The structural equation modeling approach was adopted to explore the influence of social media advertisement, technology integration, social media interaction, e-word of mouth on social media brand attitude. The structured questionnaire was adopted to gather the primary information from different types of social media users hailing from Chennai city as a study area. The samples of 614 were finalized by the adoption of non-probability convenience sampling technique. The data collected were subjected to test of normality, reliability and confirmatory factor analysis to validate the instrument. Result proves that structural equation modeling is fit for development of social media brand attitude model and further, findings show that social media advertisement, technology integration, social media integration, e-word of mouth have significant and positive influence on social media brand attitude.